2022
DOI: 10.1007/s40894-022-00185-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Youth Mental Health, Psychological Wellbeing, and Substance Use During the COVID-19 Pandemic: A Rapid Review

Abstract: Since the onset of the COVID-19 pandemic, researchers around the world have made efforts to assess its impact on youth mental health; however, the breadth of this topic has impeded a clear assessment of pandemic outcomes. This study aimed to address this gap by reviewing changes in youth (age ≤ 25) mental health, psychological wellbeing, substance use, and the use or delivery of relevant services during the pandemic. PubMed and Embase were searched in May 2021 to conduct a rapid review of the literature. The r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 146 publications
(292 reference statements)
2
47
0
Order By: Relevance
“…In addition, some studies have reported that girls and older children (13-15 compared to 6-12 years old) may be more strongly impacted by the pandemic (Panchal et al, 2021), but as pre-pandemic data are often missing, it is hard to conclude whether these are COVID-specific or general effects. Indeed, systematic reviews and meta-analyses conclude that the mental health of children worldwide was negatively affected during the first year of the COVID-19 pandemic (Ma et al, 2021;Panchal et al, 2021;Samji et al, 2022;Zolopa et al, 2022), but these interpretations were mostly based upon cross-sectional studies performed during the pandemic. Prospective studies on child mental health during the pandemic that include pre-pandemic measurements are scarce but do seem to confirm that predominantly affective problems such as depressive, anxious, and stress symptoms worsened in the first months after the onset of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies have reported that girls and older children (13-15 compared to 6-12 years old) may be more strongly impacted by the pandemic (Panchal et al, 2021), but as pre-pandemic data are often missing, it is hard to conclude whether these are COVID-specific or general effects. Indeed, systematic reviews and meta-analyses conclude that the mental health of children worldwide was negatively affected during the first year of the COVID-19 pandemic (Ma et al, 2021;Panchal et al, 2021;Samji et al, 2022;Zolopa et al, 2022), but these interpretations were mostly based upon cross-sectional studies performed during the pandemic. Prospective studies on child mental health during the pandemic that include pre-pandemic measurements are scarce but do seem to confirm that predominantly affective problems such as depressive, anxious, and stress symptoms worsened in the first months after the onset of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic context presents remarkable psychological and emotional challenges for adolescents and young adults ( Zolopa et al, 2022 ). Worries related with the possible consequences of a new disease, as well as the limitations of social interactions, particularly influenced young people lives ( Brasso et al, 2022 ).…”
mentioning
confidence: 99%
“…Larger epidemics have now passed. However, sporadic outbreaks have repeatedly stimulated recollection of this painful experience, causing traumatic stress psychological disorder [28,29].…”
Section: Traumatic Psychological Problems In the Aftermath Of The Pan...mentioning
confidence: 99%